Decomposition of Labor Productivity Growth of ASEAN9 Moderating by Economic Performance - Jee, Kouk Hiong; Rossazana, Ab-Rahim (2022)
A deficit of 2.43% or 7.1 times lower than global in labor productivity growth in 2020 after the outbreak of COVID-19 pandemic is an alarming economic issue for ASEAN. Therefore, a study was carried out to investigate the influence of decomposed components on the labor productivity growth for ASEAN9 and moderated by the effects of the economic growth over 1990-2019. The result confirmed ASEAN9 no longer a capital intensive economy whereas total factor productivity growth become most profound source in influencing the labor productivity growth of ASEAN9 both in region and country level. Surprisingly, human development index was found negatively and significantly influence the labor productivity growth of ASEAN. Besides, economic growth was empirically found has a significant moderating effect on the influence of total factor productivity growth and capital deepening on labor productivity growth in ASEAN9. In depth, 1% of increment in real GDP growth during low level of economic growth will improve the ability of capital deepening and total factor productivity growth in increasing the labor productivity growth as much as 15.89% and 47.55% for ASEAN9 respectively. Based on the obtained results, ASEAN9 are suggested to improve the technology progress and provide training to improve the productivity among the elderly. Nevertheless, the existing policy on labor productivity growth betterment in ASEAN9 should be customized according to the economic performance of the country. For the example, ASEAN should implement a policy to improve the technological progress during economic crisis rather than capital deepening.